2014
DOI: 10.1016/j.str.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotides and Substrates Trigger the Dynamics of the Toc34 GTPase Homodimer Involved in Chloroplast Preprotein Translocation

Abstract: GTPases are molecular switches that control numerous crucial cellular processes. Unlike bona fide GTPases, which are regulated by intramolecular structural transitions, the less well studied GAD-GTPases are activated by nucleotide-dependent dimerization. A member of this family is the translocase of the outer envelope membrane of chloroplast Toc34 involved in regulation of preprotein import. The GTPase cycle of Toc34 is considered a major circuit of translocation regulation. Contrary to expectations, previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 60 publications
(100 reference statements)
2
14
0
Order By: Relevance
“…Results from different research groups have generated differing models. In vitro analyses suggest that preprotein binding induces the dissociation of Toc34 dimers and promotes the exchange of bound GDP for GTP (Oreb et al, 2011;Lumme et al, 2014;Holbrook et al, 2016), suggesting that preproteins may initially bind to the GDP-bound Toc34 dimer and then act like a GTP/GDP exchange factor (GEF) for Toc34 by inducing dimer dissociation Oreb et al, 2011). Interestingly, many GEFs interact extensively with the switch II region of their target GTPase (Cherfils and Chardin, 1999;Cherfils and Zeghouf, 2013), and our results here also showed preproteins contacting switch II of AtToc159G.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Results from different research groups have generated differing models. In vitro analyses suggest that preprotein binding induces the dissociation of Toc34 dimers and promotes the exchange of bound GDP for GTP (Oreb et al, 2011;Lumme et al, 2014;Holbrook et al, 2016), suggesting that preproteins may initially bind to the GDP-bound Toc34 dimer and then act like a GTP/GDP exchange factor (GEF) for Toc34 by inducing dimer dissociation Oreb et al, 2011). Interestingly, many GEFs interact extensively with the switch II region of their target GTPase (Cherfils and Chardin, 1999;Cherfils and Zeghouf, 2013), and our results here also showed preproteins contacting switch II of AtToc159G.…”
Section: Discussionsupporting
confidence: 59%
“…It has been shown that transit peptides also reduce the dimerization of Toc34 (Oreb et al, 2011;Lumme et al, 2014;Holbrook et al, 2016), suggesting that the two GTPases may interact with preproteins in a similar manner. Furthermore, by comparing the monomeric conformation of Arabidopsis AtToc33G with the dimeric conformation of pea Toc34G, it was noted that significant conformational differences exist between the monomeric and dimeric forms in switch II (Koenig et al, 2008a).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the Anfinsen dogma, it became customary to explain function in terms of a single conformation or of well-defined transitions between a few conformations defined at atomic resolution. While this is certainly a reasonable approximation in some cases [75][76][77], availability of distance distributions demonstrates that rather often conformation transitions are coupled to order-disorder transitions or are shifts in disorder equilibria [39,[78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94]. Among the systems addressed by PDS to date, the fraction where at least one state is genuinely disordered is surprisingly large.…”
Section: A Fuzzy Relation Of Structure To Functionmentioning
confidence: 99%
“…Likewise, the homodimeric multidrug ABC transporter LmrA undergoes a disorder-order transition from a very broad conformational ensemble to a rather well-defined conformation upon nucleotide binding [80]. However, in the Toc34 GTPase homodimer, the GDP-bound state is tight and ordered and the GTB-bound state disordered [85]. In helicase PcrA from superfamily 1, the two motor domains are flexible with respect to each other in the apo-and ADP-bound states, while ATP-analogue binding brings them closer together and tightens the conformational bundle [94].…”
Section: A Fuzzy Relation Of Structure To Functionmentioning
confidence: 99%
“…It has been shown that Toc34 dimerization mutants also reduce Toc34-Toc159 interactions [73]. This has led to the hypothesis that Toc34 switches between homo- and heterodimers as part of the preprotein recognition cycle (Figure 2) [74-76]. This hypothesis also includes the proposal that Toc34 and Toc159 could reciprocally activate their GTPase activities in a so-called pseudo- trans -homodimerization mechanism [65,72], although evidence for trans -activation is lacking.…”
Section: Function Of the Toc Transloconmentioning
confidence: 99%